Occurrence of the anamorphic stage of Ophiocordyceps myrmicarum on a non-Formicidae insect in integrated crop-livestock farming systems. (August 2018) - Torres, Fabricia Zimermann Vilela; Souza, Daniela Aguiar; Lira, Ewerton da Costa; Faria, Marcos; Sujii, Edison; Lopes, Rogerio Biaggioni
Abstract: An enzootic is reported of Ophiocordyceps myrmicarum in field populations of a non-Formicidae insect, the brown shield stink bug Scaptocoris castanea (Hemiptera: Cydnidae). An on-farm epidemiological study was conducted in three previously established integrated crop-livestock systems (ICLSs), seen as sustainable approaches to farming intensification and characterized by rotation or succession of crops and pastures, as follows: (1) 4 y of annual crops (soybean in the summer and a cover crop in the winter), followed by 4 y of pasture ( Panicum maximum and Cajanus cajan consortium); (2) 4 y of pasture and 4 y of annual crops (same species as before); (3) 3 y of pasture ( Brachiaria brizantha ) and 1 y of annual crops (same as before); as well as areas with either continuous pasture ( Brachiaria decumbens ) or continuous annual crops (same as before). The incidence of this fungus on S. castanea was monitored over a 2 y period, and areawide average infection levels of nymphs and adults were in the 39.7–89.6% and 65.0–98.1% ranges, respectively. Although the number of infected bugs was positively correlated to insect density, different ICLSs had minimal influence on the incidence of the disease. This is the first report of O. myrmicarum in its anamorphic stage ( Hirsutella -like) causing infection on burrowing bugs, and the observed infection levels reported under different farming systems could lead to interest in assessment of its potential as a biological control agent of S. castanea, a severe pest of many pastures and crops in the Neotropical region. Highlights: The ant pathogen O. myrmicarum was found infecting the stink bug S. castanea . The survey showed an enzootic incidence of the fungus on insect populations. The incidence of the fungus was directly correlated to insect density in the field. Farming systems had little influence on insect density or pathogen prevalence.